Problematika Pendidikan Karakter Di MTs Al Urwatul Wutsqo Jombang - Sigit Arwin; Mujahidin (LP3M STIT Al Urwatul Wutsqo Jombang, 2021)
The purpose of this study is to describe character education at MTs Al Urwatul Wutsqo Jombang, then the problems of student character and solutions carried out by MTs Al Urwatul Wutsqo in overcoming the problems of character education. This study uses qualitative research which in the process of collecting data using observations, interviews, and documentation. Analysis of the data using data collection, data reduction, display / presentation of data, and drawing conclusions. To overcome the problems of character education, it is necessary to pay special attention from teachers and parents regarding how to talk, how to dress, student discipline, and how to get along with friends and the surrounding environment. , and alternative solutions are sought, and need to be developed more operationally so that it is easy to implement in schools.” The findings of this study are three problems of character education at MTs Al Urwatul Wutsqo Jombang, namely disciplinary problems, politeness problems and students' religious problems.